A gas diffusion layer for electrolytic cell and preparation method thereof

By using a pore-forming agent with a gradient decomposition temperature in titanium powder, a uniform and suitable pore structure is formed, the problem of pore disorder in the existing gas diffusion layer is solved, efficient water-gas transmission and gas diffusion performance is achieved, and the energy consumption of electrolyzed water is reduced.

CN119753717AActive Publication Date: 2025-04-04ANHUI BOLSMAI TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510260819.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

The internal pores of the existing gas diffusion layer for SPE electrolytic cells are messy and have poor fluid diversion effect.

Method used

A pore-making agent with a gradient decomposition temperature is used to form a pore structure with uniform distribution and suitable pore size inside the titanium powder, and a gas diffusion layer with high pore ratio and large specific surface area is prepared.

Benefits of technology

The excellent water-gas transmission performance and gas diffusion performance of the gas diffusion layer are achieved, the energy consumption of electrolyzed water is reduced, and the mechanical properties of the gas diffusion layer are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753717A_ABST
    Figure CN119753717A_ABST
Patent Text Reader

Abstract

The invention discloses a gas diffusion layer for an electrolytic cell and a preparation method thereof, which belongs to the technical field of gas diffusion layer preparation. The preparation method comprises: taking large-particle titanium powder, adding a first pore-forming agent, and pressing into a blank; taking small-particle titanium powder, adding a second pore-forming agent, and obtaining a titanium powder slurry; spraying the titanium powder slurry onto the surface of the blank and extruding it to obtain a precursor; heating the precursor to 90-130°C at a rate of 5-10°C / min under vacuum conditions, and keeping the temperature; then heating the precursor to 230-280°C at a rate of 10-15°C / min, keeping the temperature, and finally heating the precursor to 1100-1300°C at a rate of 20-30°C / min, keeping the temperature, and obtaining the gas diffusion layer. The gas diffusion layer has the advantages of high porosity and large specific surface area, and the gas diffusion layer has a gradient pore structure inside, has excellent water vapor transmission performance, and can effectively solve the problems of the existing gas diffusion layer having disordered internal pores and poor fluid backflow effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas diffusion layer preparation, and in particular relates to a gas diffusion layer for an electrolytic cell and a preparation method thereof. Background Art

[0002] Hydrogen production by electrolysis is a new type of energy storage method and one of the methods that can consume renewable resources on a large scale. It has been unanimously recognized in the world. The methods of hydrogen production by electrolysis are mainly divided into traditional alkaline water electrolysis and emerging solid electrolyte (SPE) water electrolysis. SPE water electrolysis has the advantages of high efficiency, small device, fast start and stop, no pollution, and high purity of hydrogen production.

[0003] The main components of the SPE electrolyzer are bipolar plates, gas diffusion layers (cathode and cathode), and membrane electrodes. The main functions of the gas diffusion layer are to protect the membrane electrode, conduct electricity, and guide gas and liquid. Due to the strong oxidizing properties of the anode oxygen evolution reaction during the water electrolysis reaction, the gas diffusion layer and bipolar plates of the SPE electrolyzer are mostly made of titanium metal.

[0004] The existing gas diffusion layer for SPE electrolyzer mainly adopts titanium foam plate. The titanium foam plate as the gas diffusion layer has disordered internal pores and poor fluid conduction effect. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a gas diffusion layer for an electrolytic cell and a preparation method thereof. The gas diffusion layer has the advantages of high porosity and large specific surface area, and has a gradient pore structure inside the gas diffusion layer, and has excellent water vapor transmission performance, which can effectively solve the problem of the existing gas diffusion layer having disordered internal pores and poor fluid backflow effect.

[0006] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is: A method for preparing a gas diffusion layer for an electrolytic cell comprises the following steps: (1) Take large-particle titanium powder, add the first pore-forming agent and ethanol, stir and mix, and then press into a blank; (2) Take small-size titanium powder, add a second pore-forming agent and ethanol, stir and mix, and prepare a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -3 -1×10 -4Under a vacuum degree of 1.3 Pa, the temperature is increased to 90-130°C at a rate of 5-10°C / min and kept warm for 20-40 minutes; then the temperature is increased to 230-280°C at a rate of 10-15°C / min and kept warm for 30-60 minutes; finally, the temperature is increased to 1100-1300°C at a rate of 20-30°C / min and kept warm for 90-180 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0007] Furthermore, in step (1), the particle size of the large-particle titanium powder is 50-150 μm.

[0008] Furthermore, in step (1), the first pore-forming agent comprises ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000 is 1-2:1-2:1-2:1-2.

[0009] Furthermore, in step (1), the amount of the first pore-forming agent used is 5-15% of the mass of the large-particle titanium powder.

[0010] Furthermore, the thickness of the blank in step (1) is 0.25-2.5 mm.

[0011] Furthermore, the particle size of the small-particle titanium powder in step (2) is 5-25 μm.

[0012] Furthermore, in step (2), the second pore-forming agent comprises ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000 is 1-2:1-2:2-4:2-4.

[0013] Furthermore, in step (2), the amount of the second pore-forming agent used is 5-15% of the mass of the small-particle titanium powder.

[0014] Furthermore, in step (3), the spraying thickness of the titanium powder slurry is 0.3-1 mm.

[0015] A gas diffusion layer for an electrolytic cell is prepared by the above method.

[0016] The beneficial effects produced by the present invention are: In the preparation process of the present invention, a pore former with a gradient decomposition temperature is added to the titanium powder, so that during the sintering process, the pore formers with different decomposition temperatures are decomposed step by step, forming a pore structure with uniform distribution and suitable pore diameter inside the titanium powder, wherein the internal porosity is as high as 50.4%, and the pore diameter is between 10-100 μm; the gas diffusion layer has a large specific surface area, and has good transmission performance and gas diffusion performance for water vapor.

[0017] The gas diffusion layer in the present invention has a gradient pore structure. The micropores can inhibit the aggregation of bubbles on the membrane electrode surface, and the macropore structure is conducive to the transmission of liquid from the bipolar plate to the electrode surface. The combination of the two pore structures can promote gas-liquid transfer and reduce the energy consumption of water electrolysis.

[0018] The thickness of the gas diffusion layer in the present invention can be prepared to be 0.25-2.8 mm as required, the surface roughness is less than 30 μm, the porosity of the large pore layer is 50.4%, the average pore size is 18 μm, the porosity of the small pore layer is 38.9%, the average pore size is 12 μm, and the overall tensile strength of the gas diffusion layer of different thicknesses is 0.6-2.0 KN / 50 mm, which has good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a low magnification transmission electron microscope scanning image of the cross section of the gas diffusion layer in Example 1; Figure 2 is a high magnification transmission electron microscope scanning image of the cross section of the gas diffusion layer in Example 1; Figure 3 This is a transmission electron microscope scanning image of the large-pore gas diffusion layer in Example 1; Figure 4 This is a statistical diagram of the pore size distribution of the gas diffusion layer in Example 1. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0021] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0022] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0023] The features and performance of the present invention are further described in detail below in conjunction with the embodiments and drawings.

[0024] Example 1 A gas diffusion layer for an electrolytic cell, the preparation method of which comprises the following steps: (1) Take a large-particle titanium powder with a particle size of 100 μm, add a first pore-forming agent and ethanol, which is 10% by weight of the large-particle titanium powder, wherein the first pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500 is 2:2:2:1, and the amount of ethanol is 15% by weight of the large-particle titanium powder, stir and mix, and then press into a billet with a thickness of 1.5 mm; (2) Take a small-particle titanium powder with a particle size of 10 μm, add a second pore-forming agent and ethanol, which is 10% of the weight of the small-particle titanium powder, wherein the second pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500 is 1:1:2:3, and the amount of ethanol is 30% of the weight of the small-particle titanium powder, stir and mix to obtain a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank with a spraying thickness of 1 mm, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -3 Under vacuum, the temperature was raised to 110°C at a rate of 7°C / min and kept warm for 30 minutes; then the temperature was raised to 250°C at a rate of 12°C / min and kept warm for 60 minutes; finally, the temperature was raised to 1200°C at a rate of 25°C / min and kept warm for 160 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0025] Example 2 A gas diffusion layer for an electrolytic cell, the preparation method of which comprises the following steps: (1) Take a large-particle titanium powder with a particle size of 50 μm, add a first pore-forming agent and ethanol in an amount of 15% of the mass of the large-particle titanium powder, wherein the first pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 200, polyethylene glycol with a molecular weight of 1000, and polyethylene glycol with a molecular weight of 3000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 200, polyethylene glycol with a molecular weight of 1000, and polyethylene glycol with a molecular weight of 3000 is 1:1:1:1, and the amount of ethanol is 15% of the weight of the large-particle titanium powder, stir and mix, and then press into a billet with a thickness of 0.25 mm; (2) taking a small-particle titanium powder with a particle size of 5 μm, adding a second pore-forming agent and ethanol, which is 15% by weight of the small-particle titanium powder, wherein the second pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 200, polyethylene glycol with a molecular weight of 1000, polyethylene glycol with a molecular weight of 3000 and ethanol, wherein the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 200, polyethylene glycol with a molecular weight of 1000 and polyethylene glycol with a molecular weight of 3000 is 1:1:2:2, and the amount of ethanol is 30% by weight of the small-particle titanium powder, stirring and mixing to obtain a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank with a spraying thickness of 0.3 mm, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -4 Pa vacuum, the temperature was raised to 90°C at a rate of 5°C / min and kept warm for 40 minutes; then the temperature was raised to 230°C at a rate of 10°C / min and kept warm for 60 minutes, and finally the temperature was raised to 1100°C at a rate of 20°C / min and kept warm for 180 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0026] Example 3 A gas diffusion layer for an electrolytic cell, the preparation method of which comprises the following steps: (1) Take a large-particle titanium powder with a particle size of 150 μm, add a first pore-forming agent and ethanol, which is 5% by weight of the large-particle titanium powder, wherein the first pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 600, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 600, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 4000 is 2:1:2:1, and the amount of ethanol is 15% by weight of the large-particle titanium powder, stir and mix, and then press into a billet with a thickness of 2.5 mm; (2) Take a small-particle titanium powder with a particle size of 25 μm, add a second pore-forming agent and ethanol, which is 5% by weight of the small-particle titanium powder, wherein the second pore-forming agent comprises a mixture of ammonium bicarbonate, polyethylene glycol with a molecular weight of 600, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 600, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 4000 is 1:1:4:4, and the amount of ethanol is 30% by weight of the small-particle titanium powder, stir and mix to obtain a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank with a spraying thickness of 0.8 mm, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -4 Pa vacuum degree, the temperature was raised to 130°C at a rate of 10°C / min and kept warm for 20 minutes; then the temperature was raised to 280°C at a rate of 15°C / min and kept warm for 30 minutes, and finally the temperature was raised to 1300°C at a rate of 30°C / min and kept warm for 90 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0027] Example 4 A gas diffusion layer for an electrolytic cell, the preparation method of which comprises the following steps: (1) Take a large-particle titanium powder with a particle size of 100 μm, add a first pore-forming agent and ethanol in an amount of 12% of the mass of the large-particle titanium powder, wherein the first pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 400, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 400, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 4000 is 2:2:1:1, and the amount of ethanol is 15% of the weight of the large-particle titanium powder, stir and mix, and then press into a billet with a thickness of 1 mm; (2) Take a small-particle titanium powder with a particle size of 15 μm, add a second pore-forming agent and ethanol, which is 8% by weight of the small-particle titanium powder, wherein the second pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 600, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 3000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 600, polyethylene glycol with a molecular weight of 2000, and polyethylene glycol with a molecular weight of 3000 is 2:2:4:2, and the amount of ethanol is 30% by weight of the small-particle titanium powder. Stir and mix to obtain a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank with a spraying thickness of 0.5 mm, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -4Pa vacuum, the temperature was raised to 110°C at a rate of 8°C / min and kept warm for 40 minutes; then the temperature was raised to 250°C at a rate of 15°C / min and kept warm for 50 minutes, and finally the temperature was raised to 1300°C at a rate of 20°C / min and kept warm for 120 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0028] Comparative Example 1 A gas diffusion layer for an electrolytic cell, the preparation method of which comprises the following steps: (1) Take a large-particle titanium powder with a particle size of 100 μm, add a first pore-forming agent and ethanol at a weight of 10% of the weight of the large-particle titanium powder, wherein the first pore-forming agent is polyethylene glycol with a molecular weight of 1500, and the amount of ethanol is 15% of the weight of the large-particle titanium powder, stir and mix, and then press into a billet with a thickness of 1.5 mm; (2) Take a small-particle titanium powder with a particle size of 10 μm, add a second pore-forming agent and ethanol at a weight of 10% of the weight of the small-particle titanium powder, wherein the second pore-forming agent is polyethylene glycol with a molecular weight of 3500, and the amount of ethanol is 30% of the weight of the small-particle titanium powder, stir and mix, and prepare a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank with a spraying thickness of 1 mm, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -3 Under vacuum, the temperature was raised to 110°C at a rate of 7°C / min and kept warm for 30 minutes; then the temperature was raised to 250°C at a rate of 12°C / min and kept warm for 60 minutes; finally, the temperature was raised to 1200°C at a rate of 25°C / min and kept warm for 160 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0029] Comparative Example 2 A gas diffusion layer for an electrolytic cell, the preparation method of which comprises the following steps: (1) Take a large-particle titanium powder with a particle size of 100 μm, add a first pore-forming agent and ethanol, which is 10% by weight of the large-particle titanium powder, wherein the first pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500 is 2:2:2:1, and the amount of ethanol is 15% by weight of the large-particle titanium powder, stir and mix, and then press into a billet with a thickness of 1.5 mm; (2) Take a small-particle titanium powder with a particle size of 10 μm, add a second pore-forming agent with a weight of 10% of the small-particle titanium powder, the second pore-forming agent is prepared by mixing ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500, the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 500, polyethylene glycol with a molecular weight of 1500, and polyethylene glycol with a molecular weight of 3500 is 1:1:2:3, the amount of ethanol used is 30% of the weight of the small-particle titanium powder, stir and mix, and prepare a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank with a spraying thickness of 1 mm, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -3 Under vacuum, the temperature was raised to 200°C at a rate of 13°C / min and kept for 60 minutes; then the temperature was raised to 600°C at a rate of 20°C / min and kept for 90 minutes; finally the temperature was raised to 1200°C at a rate of 25°C / min and kept for 240 minutes to obtain a gas diffusion layer for an electrolytic cell.

[0030] Test example Taking the gas diffusion layers prepared in Example 1, Comparative Example 1 and Comparative Example 2 as examples, the porosity of the gas diffusion layer was measured by X-ray diffraction, the average pore size of the gas diffusion layer was measured by mercury intrusion, and the tensile strength of the gas diffusion layer was measured by an electronic universal testing machine. The specific test results are shown in Table 1; Table 1: Gas diffusion layer measurement results It can be seen from the data in the above table that, under the condition of the same thickness, the porosity and average pore size of the gas diffusion layer prepared by the method in Example 1 are greater than those of the gas diffusion layers in Comparative Examples 1 and 2, and the tensile strength is slightly less than that of the gas diffusion layers in Comparative Examples 1 and 2; Compared with Example 1, Comparative Example 1 only uses one pore-forming agent. Since the decomposition temperature range of the single pore-forming agent is relatively narrow, it will affect the pore formation inside the gas diffusion layer during the preparation process, thereby reducing the average pore size and porosity of the gas diffusion layer. Moreover, since there are fewer pores inside the material, the tensile strength of the gas diffusion layer is increased.

[0031] Compared with Example 1, Comparative Example 2 adjusted the heating rate and insulation temperature of the calcination process. It is speculated that this may be due to the use of pore-forming agents with different decomposition temperatures. After the heating rate and insulation temperature are adjusted, the pore-forming agent cannot fully exert its pore-forming ability, thereby affecting the performance of the gas diffusion layer.

[0032] Figure 1 is a transmission electron microscope scanning image of the cross section of the gas diffusion layer in Example 1, wherein: Figure 1 This is a transmission electron microscope scanning image at a low magnification. It can be seen that the gas diffusion layer prepared in Example 1 has a small-pore membrane layer structure and a large-pore body structure, and the two-layer structure forms an obvious gradient pore structure; Figure 2 for Figure 1 High magnification transmission electron microscope scan of the structure in the blue circle. Figure 2 The structure in the red circle shows that the titanium structures between the two layers are intertwined and have a high connection strength.

[0033] Figure 3 This is a transmission electron microscope scanning image of the large-pore gas diffusion layer in Example 1. It can be seen that there are a large number of pore structures inside it, and the pores are interconnected.

[0034] Figure 4 The pore size distribution statistics of the gas diffusion layer in Example 1, wherein the red area is surrounded by the red curve (differential mercury injection increment-pore length) and the abscissa, indicating the accumulation of differential mercury injection increments within different pore size ranges, and intuitively reflects the total volume contribution of mercury entering the pore per unit length and per unit mass of material in each pore size segment during the mercury injection process. It can be seen from the figure that within a smaller pore size range (about 2-10 μm), the red area is larger, indicating that the accumulation of differential mercury injection increments within this pore size range is larger, That is, the pores of the material within this pore size range contribute more to the amount of mercury injection. As the pore size increases, the differential mercury injection increment first decreases and then fluctuates slightly around 90μm, indicating that the difficulty of mercury injection varies with pore sizes. It can also be seen from the figure that the material has a porosity of 43.58%, rich pores, an average pore size of about 18μm, and most pore sizes are concentrated between 7-30μm. The pore volume with a pore size less than 60μm accounts for as much as 70.26%, which is the main pore size range of the material, and the surface material is mainly composed of small-diameter pores.

Claims

1. A method for preparing a gas diffusion layer for an electrolytic cell, characterized in that: The following steps are involved: (1) Take large-particle titanium powder, add the first pore-forming agent and ethanol, stir and mix, and press into a blank; (2) Take small-size titanium powder, add a second pore-forming agent and ethanol, stir and mix, and prepare a titanium powder slurry; (3) Spraying titanium powder slurry onto the surface of the blank, and then extruding the surface of the titanium powder slurry to obtain a precursor; (4) Place the precursor at 1×10 -3 -1×10 -4 Under a vacuum degree of 1.3 Pa, the temperature is increased to 90-130°C at a rate of 5-10°C / min and kept warm for 20-40 minutes; then the temperature is increased to 230-280°C at a rate of 10-15°C / min and kept warm for 30-60 minutes; finally, the temperature is increased to 1100-1300°C at a rate of 20-30°C / min and kept warm for 90-180 minutes to obtain a gas diffusion layer for an electrolytic cell.

2. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: The particle size of the large-particle titanium powder in step (1) is 50-150 μm.

3. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: In step (1), the first pore-forming agent includes ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000 is 1-2:1-2:1-2:1-2.

4. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: The amount of the first pore-forming agent used in step (1) is 5-15% of the mass of the large-particle titanium powder.

5. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: The thickness of the blank in step (1) is 0.25-2.5 mm.

6. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: The particle size of the small-particle titanium powder in step (2) is 5-25 μm.

7. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: In step (2), the second pore-forming agent includes ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000, and the mass ratio of ammonium bicarbonate, polyethylene glycol with a molecular weight of 200-600, polyethylene glycol with a molecular weight of 1000-2000 and polyethylene glycol with a molecular weight of 3000-4000 is 1-2:1-2:2-4:2-4.

8. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: The amount of the second pore-forming agent used in step (2) is 5-15% of the mass of the small-particle titanium powder.

9. The method for preparing a gas diffusion layer for an electrolytic cell according to claim 1, characterized in that: In step (3), the spraying thickness of the titanium powder slurry is 0.3-1 mm.

10. A gas diffusion layer for an electrolytic cell, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of gradient pore porous high-niobium titanium-aluminum alloy

    CN101967578A

  • Porous metal-ceramic composite material gas spreading layer used for hydrogen fuel cell and preparation method thereof

    CN102810680A

  • Preparation method of porous film

    CN106000123A

  • PEM water electrolysis cell anode porous diffusion layer and preparation method and application thereof

    CN115090879A

  • Wave energy-wind energy power generation and hydrogen production integrated system based on semi-submersible platform

    CN115848574A